The Use Of Thermography In Endovascular Surgeries - Kyjovský, Ondřej (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This article deals with the use of thermography as a support diagnostic method for the treatment of varicose veins. The principle of IRT involves the detection of infrared radiation. The main objective of the study was to compare how the temperature varies during the scanning procedure for RFA and EVLT, as well as the changing temperature of the surface of the skin before surgery and after surgery.
Keywords: thermography; radiofrequency ablation; endovenus laser ablation